Sustainability and Elderly Brain Care: Intersecting Paths: A Bibliometric and Thematic Analysis Study - Gamze Sarıkoç; Hilal Merve Belen Ünürlü (International Journal of Environmental Research and Public Health, 2026)
Background: Population aging is intensifying the burden of cognitive decline and dementia, while sustainability is becoming central to how health and care systems respond; yet the research at the intersection of these two agendas has not been mapped. Methods: A bibliometric and thematic analysis was conducted on 1100 documents retrieved from the Web of Science Core Collection and Scopus (2000–2026) and analyzed with the bibliometric package, combining performance analysis, science mapping, and an interpretive labelling of the keyword co-occurrence clusters. Results: The literature grew rapidly (19.9% annual growth) and was concentrated in high-income countries, with the United States and the United Kingdom as the leading collaborators. Four themes were identified: multidomain lifestyle prevention of dementia and mental health; the cognitive health continuum; caregiving and sustainable care delivery for the oldest old; and sustainability as a transversal, foundational dimension. Sustainability appeared as a basic, transversal theme rather than an explicit research focus, and quality of life recurred across the themes. Conclusions: Research on elderly brain care rests on a largely implicit foundation of sustainability. Making sustainability explicit, linking brain health to healthy–longevity and brain–capital frameworks, and broadening participation beyond high-income settings are the field’s main priorities.